Peran Guru Bahasa Indonesia, dalam Mencegah Perundungan Melalui Penanaman Nilai-Nilai Kristiani di Sekolah SMA Swasta Marisi Medan - Nova Ritonga; Erfriani Sekar Talenta Simangunsong; Kristin Dwi Amsari Pasaribu; Arlin Septia Basana Siagian; Kezia Tarila Rubina Br Sitepu; Johannes Bagas Sitorus (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
Bullying in the school environment, especially at the high school level, has become an issue that is increasingly disturbing and urgent to be addressed. Many students who are victims of bullying experience lasting negative impacts, both psychologically and socially. This phenomenon not only affects students' academic lives, but can also result in serious emotional problems, such as depression and anxiety. Therefore, it is important to find effective solutions to prevent bullying behavior in schools. In this research, researchers used interview methods to explore in-depth data about individual experiences, opinions or feelings that are difficult to measure quantitatively. The role of Indonesian language teachers is very strategic. Apart from teaching language and literature, teachers have the opportunity to instill moral values ​​through selected learning materials. Literary works, for example, often contain themes of humanity and social interaction that are relevant to bullying behavior. By integrating Christian values ​​in language learning, teachers can help students understand the importance of empathy and compassion in relationships between people. From the results of research that has been conducted, it is clear that Indonesian language teachers at Marisi Medan Private High School have a crucial role in preventing bullying through instilling Christian values.